Heart failure due to aorto-right atrial fistula and successful treatment with percutaneous closure - Anar Mammadli; Mustafa Kılıçkap; Irem Dinçer; Müge Akbulut; Tamer Sayın (KARE Publishing, 2019)
Aorto-atrial fistula is a rare anomaly of the heart that may be the result of congenital or acquired conditions, such as bacterial endocarditis, paravalvular abscess, aortic dissection, or a complication of cardiac surgery. A 50-year-old female patient presented at the clinic with the complaint of dyspnea and abdominal distention due to ascites. On admission, her functional capacity was New York Heart Association (NYHA) class III. A physical examination revealed a systolic murmur, which was best audible in the right parasternal side, ascites, and hepatomegaly. An aorto-right atrial fistula was detected using transthoracic echocardiography and confirmed with transesophageal echocardiography and aortography. The patient had a history of previous cardiac surgery, anticoagulant use, and heart failure; therefore, percutaneous intervention was preferred to surgery as a result of the high surgical risk. A successful closure of the fistula was performed with an Amplatzer Duct Occluder II device. The patient demonstrated a dramatic response to the treatment, resulting in a decrease in the ascites and halving of her diuretic dose within 1 week. Her functional capacity improved to NYHA class II, and right atrial pressure decreased to 8 mmHg after a month.